Providing Visual Aids (Posters) for English Lesson Grade One in ABC Elementary School - Johanna Limarsono (Institute of Research and Community Outreach - Petra Christian University, 2019)
This final project is based on the writer’s internship in ABC Elementary School from March 12th to June 8th, 2018. The writer thought that it was a good solution to make and provide posters as the final project because of the problem she found during her internship in ABC Elementary School, that is, students’ lack of English vocabulary. The students seemed they did not want to participate in the English learning because the English book used in class was quite difficult for grade one students. The writer created posters to provide the students learning tools so that the students can follow and participate the teaching-learning process actively. By having interesting posters with their uniqueness (3D poster, removable poster, and etcetera), the students are expected to feel more interested in knowing and learning English vocabulary. These posters can help to support the teaching-learning process. Keywords: Posters, 3D Poster, English Vocabulary, Project